The influences of knowledge loss and knowledge retention mechanisms on the absorptive capacity and performance of a MIS department. Issue 7 (15th August 2016) - Chang, Christina Ling-hsing; Lin, Tung-ching; Tsai, Wen-Chin
Abstract : Purpose: Knowledge loss impact on the performance of MIS departments due to its influence on absorptive capacity. Furthermore, knowledge retention in human resource management and information system application is also included in the research model, in order to examine their effectiveness in mitigating knowledge loss. Design/methodology/approach: Survey method and hypotheses are tested with the collected data from 191 Taiwanese IS personnel. Findings: The results not only indicate knowledge loss has impacts on the absorptive capacity and performance of MIS departments while information systems could mitigate knowledge loss, but also provide deeper understanding of knowledge loss and potential issues for academics; as for practitioners, this study could serve as a reference to design and adopt knowledge management mechanisms. Originality/value: Knowledge management is an important issue for organizations since it is the source of competitive advantages and excellent performance, although the investment in knowledge management isn't necessary effective in retaining knowledge. This study conducts survey to examine the influences of knowledge loss in MIS departments, since the high turnover rate of employees and the rapid environmental changes in technical world may worsen the situation. According to dynamic capability theory, absorptive capacity is a critical ability to have while facing turbulent environment.